Prospects of Organic Dairy Farming in India A SWOC analysis - Kale, Rajiv Baliram; Ponnusamy, K. (Indian Farming, 2018)
There is a growing awareness about harmful effects due to increasing use of chemicals by environmentalists which is giving impetus to organic farming movement. As well, consumers are also getting conscious about food safety across the world. Both government and several private agencies also have taken a lot of initiatives in promoting the organic farming and today, India is among the top ten countries of certified area under organic farming.